REVELATION - John B Chethimattam (Journal of Dharma, 1978)
Word and Revelation constitute the most obvious and yet the most sublime in interreligious terminology. Eastern religions, which emphasize experience and realization as the goal of religion, do not generally speak of revelation but insist on the centrality of the Word. According to the Rg Vedic sage Vac entered human consciousness when man started naming things. Later grammar, poetry and ritual chants, refined it. But it is discovered in its authenticity only in the heart of the sage and only the one to whom the Divine Word discloses herself can really understand her. People are brought together by the Word and their ranks are determined according to their service of the Word. Hence the Word is the symbol of intercommunion among men as, well as of their communication with God.